2019
DOI: 10.12688/f1000research.17952.2
|View full text |Cite
|
Sign up to set email alerts
|

Updating the evidence on the effectiveness of the alcohol reduction app, Drink Less: using Bayes factors to analyse trial datasets supplemented with extended recruitment

Abstract: Background: A factorial experiment evaluating the Drink Less app found no clear evidence for main effects of enhanced versus minimal versions of five components but some evidence for an interaction effect. Bayes factors (BFs) showed the data to be insensitive. This study examined the use of BFs to update the evidence with further recruitment. Methods: A between-subject factorial experiment evaluated the main and two-way interaction effects of enhanced versus minimal version of five components of Drink Less. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
0
11
1
Order By: Relevance
“…Taken together, these findings suggest that smartphone-delivered ApBM holds promise. However, since controlled trials of delivering ApBM online have found equivalent reductions in active ApBM when compared with sham training and the only prior RCT of an alcohol-reduction app that included ApBM reported null findings [ 28 ], it remains necessary to establish the efficacy of smartphone-delivered ApBM in RCTs. This is a particularly worthwhile investment given the greater convenience, flexibility, and accessibility (eg, notification reminders and immediacy of access) that can be offered via smartphones relative to web-based platforms (eg, via a PC or laptop).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, these findings suggest that smartphone-delivered ApBM holds promise. However, since controlled trials of delivering ApBM online have found equivalent reductions in active ApBM when compared with sham training and the only prior RCT of an alcohol-reduction app that included ApBM reported null findings [ 28 ], it remains necessary to establish the efficacy of smartphone-delivered ApBM in RCTs. This is a particularly worthwhile investment given the greater convenience, flexibility, and accessibility (eg, notification reminders and immediacy of access) that can be offered via smartphones relative to web-based platforms (eg, via a PC or laptop).…”
Section: Discussionmentioning
confidence: 99%
“…In the United Kingdom, Crane et al [ 27 ] tested apps containing various combinations of 5 different modules (including an ApBM module) among people drinking at hazardous levels. Despite initially reporting that combining ApBM with normative feedback reduced participants’ weekly alcohol consumption [ 27 ], they later reported a lack of evidence for efficacy after re-analyzing outcomes with a larger sample [ 28 ]. In the Netherlands, Laurens et al [ 29 ] tested an ApBM app with people who were concerned about, or wished to reduce, their drinking.…”
Section: Introductionmentioning
confidence: 99%
“…The Bayes factor analysis of additional trial outcome data (Phase 1) indicated that there was support for the null hypothesis that the ‘Identity Change’ module – helping users foster a change from seeing being a “drinker” as a key part of their identity – had no effect on past week alcohol consumption ( Garnett et al , 2019b ). These findings, alongside results from analysing user feedback (Phase 1) and usage data indicating users very rarely viewed these screens, guided the decision to remove the module.…”
Section: Resultsmentioning
confidence: 99%
“…Bayes factors also allow researchers to ‘top-up’ their results from one trial with additional data collected ( Rouder, 2014 ). In the factorial trial, Bayes factors showed the data to be insensitive so an update was conducted to analyse additional trial outcome data collected through extended recruitment (published in full elsewhere ( Garnett et al , 2019b )). After the required sample size was reached (n = 672), additional data from new participants (n = 1914) were collected over five months (available in Underlying data: https://osf.io/nad4e ) Bayes factors with a half-normal distribution and priors set to the point estimates from the initial 672 participants were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…One, targeting internet help-seekers with harmful levels of alcohol use (15 or more drinks/week), did not find any effects over 6 months, although some benefit appeared to occur among those who actually downloaded the app (23). A fourth smartphone app, Drink Less, evaluated among adult help-seekers with at least hazardous alcohol use who all downloaded the app, showed declines in alcohol use over time among all participants, where self-monitoring and feedback combined led to use of more app sessions (24); secondary analysis using Bayes factors showed weak evidence for an interactive combined effect of four components (normative feedback, cognitive bias retraining, self-monitoring and feedback, and action planning) yielding lower alcohol consumption (25).…”
Section: Introductionmentioning
confidence: 96%